Perancangan Model Ontologi untuk Silsilah Keluarga Puri Agung Peliatan - Palguna, I Wayan Gede Adi; Pramartha, Cokorda Rai Adi; Putri, Luh Arida Ayu Rahning (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 1 (2022): JNATIA Vol. 1, No. 1, November 2022, 2022)
Family tree is a diagram representing family relationships that usually contains records describing family origins and family relationships over several generations. Puri was the center of government of the Balinese kingdoms in ancient times as well as designation for the residence of Balinese nobles, especially those who still have blood relations with Balinese kings. Even though it has been around for a long time, the lack of information and track record creates a need for very important information. For this reason, ontology plays a role in representing knowledge explicitly. Ontology is the backbone of the semantic web, which is a technology that allows machine to understand the content of information. The development of ontology model uses Methontology method which has advantage related to the description of each activities. Methontology allows to integrate the ontology model that has been built previously for further development. Silsilah Keluarga Puri Agung Peliatan’s ontology produces 14 classes, 25 object properties, 8 data properties, and 15 instances. The ontology evaluation procedure using SPARQL queries also yields suitable outcomes.